ANALISA STABILITAS DINDING PENAHAN TANAH UNTUK MENGANTISIPASI LONGSORAN PADA LERENG JALAN TOL AKSES MNP - Bustamin Abdul Razak; Ade Mallombasang (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This study aims to obtain the dimensions of the retaining wall and obtain the safety factor against shearing, overturning, and the bearing capacity of the soil. The data used for the design of the retaining wall in this study are traffic load, slope and soil test data. The traffic load used is 10 kN/m2. Based on the results of soil testing, the parameters of soil density, cohesion and internal shear angle were obtained from the fill and subgrade soil. The retaining wall is designed with a width of 3.4 meters and a total height of 5.5 meters with a slope angle of 20 degrees. The retaining wall material is designed from concrete. The collapse of the retaining wall structure is influenced by the forces of traffic and soil loads behind the retaining wall. To withstand this force, the stability of the retaining wall structure is reviewed for the effect of gravity on the retaining wall structure and the soil in front of the retaining wall leg. Stability to overturning obtained Fgl of 9.697, stability to shear obtained Fgs of 3.255 and stability to failure of soil bearing capacity obtained 35.820. From the three stability reviews, it shows that the retaining wall structure meets the requirements for safety against working loads.